FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN INVESTASI SAHAM (STUDI KASUS : PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI) - Azmir Ferdinansyah; Rudy Chairudin; Lusia Nargis; Mariyam Zanariah (JURNAL KOMPETITIF, 2022)
This research is an empirical study to test how the company's internal factors which include the cash ratio, debt equity ratio, EPS, ROI and the company's external factors which include the SBI interest rate and stock beta can contribute to stock investment decisions in this case measured by the DPR. The sample technique used was purposive sampling in order to obtain a total sample of 26 companies. The analysis technique used in this study is multiple linear regression and hypothesis testing used in this study t-statistics to test the partial regression coefficients and F-statistics to test the feasibility of the research model with a Level of Significance of 5%. In addition, the classical assumption test was also carried out. The results of the analysis show that based on the hypothesis testing that has been carried out, it is found that CR, DER, EPS, ROI, SBI Interest Rates and Stock Beta simultaneously have a significant effect on the investment decision (DPR) of Manufacturing companies. Partially only CR, EPS, and ROI are able to have a partially positive and significant influence on investment decisions (DPR).Keywords: CR, DER, EPS, ROI, SBI Interest Rate and Stock Beta, (DPR)